Phytochemistry and Antioxidant Activity of Aerial Parts of Phagnalon sordidum L. - Cherchar, Hanene; Faraone, Immacolata; DʼAmbola, Massimiliano; Sinisgalli, Chiara; Dal Piaz, Fabrizio; Oliva, Patrizia; Kabouche, Ahmed; Kabouche, Zahia; Milella, Luigi; Vassallo, Antonio (Planta Medica, 2019)
One new natural monoterpene, 5-O-β-d-glucopyranosyl-2-hydroxy-p-cymene (1), and 11 known compounds were isolated through a biologically oriented approach from the aerial parts of Phagnalon sordidum L. The most active extract and fractions were selected using 3 complementary antioxidant activity assays. Results and the different methods were compared by relative antioxidant capacity index. In addition, the most active extract of P. sordidum was subjected to liquid chromatography coupled with electrospray ionization hybrid linear ion trap quadrupole Orbitrap mass spectrometry to quantify secondary metabolites. Antioxidant activities of ethyl acetate extract, and purified 3,4-dihydroxyacetophenone (3) and nebrodenside A (7) were demonstrated by in vitro cell free model assays, and their protective effect against H2O2-induced oxidative stress in a HepG2 (human hepatocellular carcinoma) cell line was established.
Keywords: Phagnalon sordidum; Asteraceae; phenolic derivatives; antioxidant activity; mass spectrometry